Knowledge and Practices among Female Nurses on Insertion and Care of Indwelling Urinary Catheter to Female Patients in a Selected Teaching Hospital in Sri Lanka - Rohan, P.; Amarasekara, T. D. (My University, 2019)
Globally, catheter-associated urinary tract infection (CAUTI) is one of the most common hospital-acquired infections. By following proper guidelines and recommended practice regarding insertion and care of indwelling urinary catheter, one could prevent and reduce CAUTI. Knowledge and practices among nurses regarding the insertion and care of indwelling urinary catheter in female patients are highly essential to minimize complications related to indwelling urinary catheter among female patients. There are limited data available on this phenomenon in Sri Lanka. The purpose of this study was to determine knowledge and practices among nurses regarding the insertion and care of indwelling urinary catheter in female patients at a selected teaching hospital. A descriptive cross-sectional design was conducted among conveniently selected 122 nurses from a teaching hospital. A pre-tested (n=10), a semi-structured questionnaire, was used to collect data. Ethical approval was obtained from the ethics review committees of the Faculty of Medical Sciences, University of Sri Jayewardenepura, and Colombo South Teaching Hospital, Sri Lanka. Findings revealed that only 36% of the participants had a satisfactory